Latin America in PISA 2012: Factors related with mathematical literacy - Fernández Aráuz, Andrés (2017)
Eight countries in Latin America participated in the PISA 2012 assessment, obtaining poor results in mathematics assessment. In analyzing the factors associated with this performance, the results of this research show that attendance at preschool education plays an important role in the future student performance. Moreover, even controlling for variables traditionally associated with performance as the socioeconomic status of the household or the educational level of parents, this research shows that personal factors have a great importance when explaining the differences in outcomes: self-concept students in the math area, their interest towards mathematics and familiarity with mathematical concepts are variables that were significant to predict scores on the PISA test.